2022
DOI: 10.3389/fphys.2022.1019028
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels as a therapeutic target for renal fibrosis

Abstract: Renal ion channel transport and electrolyte disturbances play an important role in the process of functional impairment and fibrosis in the kidney. It is well known that there are limited effective drugs for the treatment of renal fibrosis, and since a large number of ion channels are involved in the renal fibrosis process, understanding the mechanisms of ion channel transport and the complex network of signaling cascades between them is essential to identify potential therapeutic approaches to slow down renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 304 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that dysregulation of water and electrolyte transport in the kidney contributes to the progression of fibrosis and inflammation. For example, disrupted sodium transport can lead to tubular injury and activation of pro-inflammatory pathways as well as renal fibrosis [ 30 ]. As previously discussed, AQP1 plays a critical role in both tubular injury and the subsequent healing process [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dysregulation of water and electrolyte transport in the kidney contributes to the progression of fibrosis and inflammation. For example, disrupted sodium transport can lead to tubular injury and activation of pro-inflammatory pathways as well as renal fibrosis [ 30 ]. As previously discussed, AQP1 plays a critical role in both tubular injury and the subsequent healing process [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Localizing β subunits within specific cells provides valuable insights into the function of BK in these cells (Tricarico et al, 1997). The BK channel in the renal connecting tubule expresses the β2 subunit and deleting this subunit in mice has resulted in high renal potassium retention and hyperkalemia (Yan et al, 2022). Additionally, β4 KO have resulted in low potassium excretion, mild hypertension, and mild fluid retention in mice treated with a high-potassium diet (Grimm et al, 2009).…”
Section: Bk Channel In the Vascular Systemmentioning
confidence: 99%
“…The BK channel is activated indirectly by shear stress in the kidney through coupling to TRPV4 channel activation and their role in Ca 2+ influx in endothelial cells (Reiter et al, 2006). Recent observations have shown that some BK channel activators, such as NS1619 and BMS191011, attenuate renal fibrosis and promote proper kidney function in animal models (Yan et al, 2022).…”
Section: Bk Channel In the Vascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Other organ systems that are now areas of research focus include the liver, pancreas, sinuses, intestines, and kidneys, among others ( 9 ). The kidneys are of consequence, as they are heavily enriched in ion channels ( 10 ). Defective ion exchange due to CF dramatically changes the metabolic output of the kidney ( Figure 1 ) and the crosstalk of this with other organ systems ( 11 ).…”
Section: Trikafta Propels a New Era In Cftr Researchmentioning
confidence: 99%